1994
DOI: 10.2105/ajph.84.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Maternal attitude toward pregnancy and the risk of neonatal death.

Abstract: OBJECTIVES. Reduced options for fertility control over the past decade have increased the rates of unwanted pregnancy. We evaluated whether a woman's negative attitude toward her pregnancy increased the risk of perinatal mortality, in a large, prospective cohort study. METHODS. The association between attitude toward the pregnancy and perinatal mortality was evaluated in a longitudinal cohort study of 8823 married, pregnant patients enrolled from 1959 to 1966 in the Child Health and Development Studies. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 6 publications
1
44
0
1
Order By: Relevance
“…Children from unintended pregnancies even experience a higher risk of death in settings as diverse as the United States (Bustan and Coker 1994), Bangladesh (Chalasani, Casterline and Koenig 2007), and India (Singh, Singh and Mahapatra 2013). Though selection could account for some of this association (Bishai et al 2015), these studies offer compelling evidence that children from unintended pregnancies experience long-lasting, severe consequences.…”
Section: Unintended Pregnancy and Child Outcomesmentioning
confidence: 99%
“…Children from unintended pregnancies even experience a higher risk of death in settings as diverse as the United States (Bustan and Coker 1994), Bangladesh (Chalasani, Casterline and Koenig 2007), and India (Singh, Singh and Mahapatra 2013). Though selection could account for some of this association (Bishai et al 2015), these studies offer compelling evidence that children from unintended pregnancies experience long-lasting, severe consequences.…”
Section: Unintended Pregnancy and Child Outcomesmentioning
confidence: 99%
“…This research generally suggests that when children from wanted pregnancies are compared to those from mistimed or entirely unwanted pregnancies, the latter two groups fare worse. Unwanted (and in many instances, mistimed) pregnancy is positively associated with disadvantageous outcomes like low birth weight (Kost, Landry, and Darroch 1998), delayed prenatal care (Kost et al 1998;Marsiglio and Mott 1988;Pulley et al 2002), maternal smoking during pregnancy (Joyce et al 2000;Weller, Eberstein, and Bailey 1987), and even perinatal mortality (Bustan and Coker 1994). It is, on the other hand, negatively associated with advantageous outcomes such as breast-feeding (David 1981;Joyce et al 2000;Marsiglio and Mott 1988;Pulley et al 2002), doctor visits during the early months of life (Kost et al 1998;Marsiglio and Mott 1988), and some aspects of cognitive development (Baydar 1995;Joyce et al 2000).…”
Section: Other Relevant Researchmentioning
confidence: 99%
“…4,5 Unintended pregnancies are of particular concern because they may affect the health of the newborn through a woman's prepartum and some postpartum behavior and experiences, including greater likelihood of smoking during pregnancy, greater likelihood of insufficient folic acid intake during pregnancy, lower likelihood of breastfeeding after birth, greater likelihood of infant death in the first 28 days of life, and higher likelihood of child abuse and neglect. [6][7][8][9][10] Women who are sexually active, fertile, not pregnant, and not trying to become pregnant and who come from a medically underserved, low-income background are much more likely to demonstrate contraceptive risk taking or nonuse of contraception while being sexually active compared with the general population of fertile women at all income levels. 5,11 One study found that women who practice contraceptive risk taking had more than three times as many unwanted pregnancies as women who regularly use contraception.…”
Section: Introductionmentioning
confidence: 99%